2007
DOI: 10.1128/aem.02243-06
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Virulence in a Viable but Nonculturable Edwardsiella tarda Isolate

Abstract: Edwardsiella tarda is pathogen of fish and other animals. The aim of this study was to investigate the viable but nonculturable (VBNC) state and virulence retention of this bacterium. Edwardsiella tarda CW7 was cultured in sterilized aged seawater at 4°C. Total cell counts remained constant throughout the 28-day period by acridine orange direct counting, while plate counts declined to undetectable levels (<0.1 CFU/ml) within 28 days by plate counting. The direct viable counts, on the other hand, declined to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 55 publications
9
85
0
2
Order By: Relevance
“…GbpA, a characterized GlcNAc-binding protein, is an example of a V. cholerae colonization factor utilized in both the host and the aquatic environment . In addition, pathogenic strains of a variety of bacterial species have been characterized to retain and express virulence factors when in the VBNC state (Du et al, 2007;Fischer-Le Saux et al, 2002;Rahman et al, 1996;Smith & Oliver, 2006b), and also maintain antibiotic resistance (Kamruzzaman et al, 2010;Lleò et al, 2003). In the host environment, virulence factors such as TCP are required for colonization and persistence in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…GbpA, a characterized GlcNAc-binding protein, is an example of a V. cholerae colonization factor utilized in both the host and the aquatic environment . In addition, pathogenic strains of a variety of bacterial species have been characterized to retain and express virulence factors when in the VBNC state (Du et al, 2007;Fischer-Le Saux et al, 2002;Rahman et al, 1996;Smith & Oliver, 2006b), and also maintain antibiotic resistance (Kamruzzaman et al, 2010;Lleò et al, 2003). In the host environment, virulence factors such as TCP are required for colonization and persistence in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a visual light microscopy analysis of V. ordalii cells indicated that these were reduced in size after the third day of incubation in the sterile microcosm; however, future analysis through scanning electronic microscopy is needed to confirm this observation. Such a drastic reduction in cell size may be a survival strategy to confer resistance to environmental stress, as has been observed during the starvation survival process for several bacterial species in the aquatic environment (Amy & Morita 1983, Kjelleberg & Hermansson 1984, Jiang & Chai 1996, Vatsos et al 2003, Avendaño-Herrera et al 2006, Du et al 2007, Arias et al 2012. Also in the sterile microcosm, V. ordalii cells changed from a rod to a cocci shape.…”
Section: Discussionmentioning
confidence: 99%
“…This approach relies only on the presence of culturable cells but does not take into account that cells might still be alive, although non-culturable, after plasma treatment. This may have catastrophic consequences if microorganisms that are assumed dead, are pathogenic ones who may retain virulence even when they are nonculturable [44]. Plasma-mediated biofilm inactivation may proceed through a first step in which bacterial cells might enter a Viable-ButNon-Culturable (VBNC) state.…”
Section: Concerns About Viabilitymentioning
confidence: 99%